A Cause of Fungemia in A Patient with Hematological Malignancy: Blastoschizomyces capitatus - Müge AYHAN (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2015)
Blastoschizomyces capitatus is a rare fungal pathogen that may lead to severe and fatal infections in patients with hematological malignancies.The risk factors for infections with this pathogen are hematological malignancy, cytotoxic chemotherapy, corticosteroid use, intravascular catheter use, and broad spectrum antibiotic use. In this case report, fungemia and pneumoniae due to B. capitatus is reported in a patient who is diagnosed with acute lymphoblastic leukemia and receiving chemotheraphy. Blood cultures became negative after treatment with liposomal amphotericin B. In immunosupressed patients with severe fungal infection, B. capitatus should be kept in mind and should be considered in the choice of treatment. Further studies are required for the determination of antifungal susceptibilities and susceptibility breakpoints for B. capitatus.